Dampak Kualitas Auditor dan Tata Kelola Perusahaan terhadap Kualitas Laporan Keuangan Perusahaan - Ferry Arnanda Adhitama (Syntax Corporation Indonesia, 2025)
In Indonesia, efforts to improve corporate financial reporting standards have made corporate governance a top priority. A number of rules issued by capital market regulators, including the Indonesia Stock Exchange (IDX), the Financial Services Authority (OJK), support this, because it ensures the integrity and openness of financial reporting. The purpose of this study is to analyze the impact of auditor quality and corporate governance on the quality of company reports. The research method used was the systematic review method. Syytematic review is a methodology used in literature review, which maps the content of the literature and identifies gaps in the field of study. Sestemtic review using the PRISMA Technique. Based on the results of the review carried out, the impact of auditor quality and corporate governance on the quality of company reports is: 1) producing better quality financial statements; 2) Able to identify major errors in financial statements; 3) Have Compliance with Accounting Regulations and Standards; 4) Periodic reviews.